Design of OFDM-IM system based on IRS-assisted - Mengmeng ZHAO; Liming HE; Fangfang LIU (Dianxin kexue)
Index modulation (IM) and intelligent reflecting surface (IRS) are emerging mobile communication technologies.In order to improve the reliability of traditional orthogonal frequency division multiplexing (OFDM) system, an orthogonal frequency division multiplexing with index modulation (OFDM-IM) system based on IRS-assisted was designed.Firstly, the OFDM-IM system was designed by using spatial modulation and frequency domain modulation to increase the Euclidean distance between subcarriers.Then, by establishing an equivalent circuit model, a practical IRS model was obtained.Finally, an alternating optimization algorithm was used to optimize the active transmission power of the access point (AP) and passive beamforming of the IRS jointly.The simulation results show that compared to the benchmark scheme, the symbol error rate (SER) or bit error rate (BER) of the OFDM-IM system based on IRS-assisted can be reduced by 60%～90%.Especially in the case of high signal-to-noise ratio, the SER or BER of the system can reach 1.0×10-6, which indicates that the introduction of IM and IRS technologies has optimized the link transmission quality of end-to-end communication system.In addition, based on the IRS-assisted OFDM-IM system as the standard, simulations are conducted to demonstrate the impact of various parameters from the IRS model and IM.It concludes that the parameters in the system should be selected reasonably according to channel state information (CSI).